Coroner Investigations of Suspicious Elder Deaths; 2008-2011 (California) - Mosqueda, Laura ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This was a two phase project designed to investigate the decision-making process of the coroner/medical examiner (CME) offices who are charged with investigating suspicious elder deaths and to pilot an intervention that augmented the decision-making process in three CME offices. In phase one, researchers collected case data from CME offices, public data on elder deaths, and interviews with CME investigators. Researchers then developed a brief screening tool, Elder Suspicious Death Field Screen (ESDFS), to be used by CME employees fielding reports of elder deaths. In phase two, the ESDFS was implemented in three counties for a six-month data collection period. An expert panel reviewed a subsample of cases to assess whether CME investigators made appropriate decisions to investigate or not.